2020
DOI: 10.1002/mc.23232
|View full text |Cite
|
Sign up to set email alerts
|

SlowN‐acetylation as a possible contributor to bladder carcinogenesis

Abstract: Bladder cancer (BCa) is an exophytic tumor that presents as either noninvasive confined to the mucosa (NMIBC) or invading the detrusor muscle (MIBC), and was recently further subgrouped into molecular subtypes. Arylamines, major BCa environmental and occupational risk factors, are mainly metabolized by the genetically polymorphic N‐acetyltransferases 1, NAT1 and NAT2. In this study, we investigated the association between N‐acetyltransferases genetic polymorphism and key MIBC and NMIBC tumor biomarkers and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In this analysis, we report on potential risk modification of the relation between THM exposure and 16 loci associated with bladder cancer. Although there is evidence that -acetyltransferase 1 (NAT1) also plays a role in bladder carcinogenesis, 26 SNPs in NAT1 genotyped as part of our GWAS did not show strong evidence of association with bladder cancer risk and therefore is not presented in these results. We found the strongest evidence of such an association for rs907611 ( LSP1 region), with a suggestion of interaction in both New England and Spain.…”
Section: Discussionmentioning
confidence: 81%
“…In this analysis, we report on potential risk modification of the relation between THM exposure and 16 loci associated with bladder cancer. Although there is evidence that -acetyltransferase 1 (NAT1) also plays a role in bladder carcinogenesis, 26 SNPs in NAT1 genotyped as part of our GWAS did not show strong evidence of association with bladder cancer risk and therefore is not presented in these results. We found the strongest evidence of such an association for rs907611 ( LSP1 region), with a suggestion of interaction in both New England and Spain.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, the incidence of urinary bladder cancer has increased markedly in Lebanon and is currently the second most incident cancer among males ( Shamseddine et al, 2004 ). The frequency of 560G > A (rs4986782) (R187Q) is 7-fold higher among urinary bladder cases than controls in Lebanon ( Yassine et al, 2012 ) and is significantly associated with higher muscle-invasiveness and higher tumor grade of urinary bladder tumors ( El Kawak et al, 2020 ). In the current study 560G > A (rs4986782) (R187Q) caused a 4 to 5-fold increase ( p < 0.05) in affinity for both ABP and N-OH-ABP.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these focus on associations between NAT1*10 and/or NAT1*11 and cancer risk, two variant alleles that possess SNPs in the 3′-UTR region outside of the coding exon. Urinary bladder cancer is most frequently associated with NAT1 genetic polymorphism ( Cascorbi et al, 2001 ; Yassine et al, 2012 ; Dhaini et al, 2018 ; El-Kawak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that N-acetylation mainly affects protein-membrane binding and protein stability ( 16 ). N-acetylation is also one of many factors contributing to tumor progression; for example, slow N-acetylation is a factor in bladder carcinogenesis and muscle invasiveness, and NAT1 is recognized as a biomarker candidate in bladder cancer and a potential target for drug development point ( 17 ).…”
Section: The Components and Process Of Acetylation System In Cancersmentioning
confidence: 99%